1992
DOI: 10.1002/oca.4660130103
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of time‐delay systems by dynamic programming

Abstract: SUMMARYThe use of iterative dynamic programming employing systematic region contraction and accessible grid points is investigated for the optimal control of time-delay systems. At the time of generating the grid points for the state variables, the corresponding delayed variables at each time stage are also generated and stored in memory. Then, when applying dynamic programming, a linear approximation is used to obtain the initial profile for the delayed variables during integration. This procedure was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 12 publications
4
43
1
Order By: Relevance
“…From Table it is observed that for the time step size h = 0.004 and constant time‐delay τ ( t ) = 1, a minimum value of the cost functional is obtained as J = 4.796786. As it is shown in Table , this value of J computed by the proposed scheme is compared very well with those achieved by the single‐term Walsh series , iterative dynamic programming , Legendre multi‐wavelets , modified line‐up competition algorithm and recursive shooting method . Comparison results reveal the validity of the proposed FD method for solving the TDOCP ()–().…”
Section: The Second‐order Two‐step Fd Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…From Table it is observed that for the time step size h = 0.004 and constant time‐delay τ ( t ) = 1, a minimum value of the cost functional is obtained as J = 4.796786. As it is shown in Table , this value of J computed by the proposed scheme is compared very well with those achieved by the single‐term Walsh series , iterative dynamic programming , Legendre multi‐wavelets , modified line‐up competition algorithm and recursive shooting method . Comparison results reveal the validity of the proposed FD method for solving the TDOCP ()–().…”
Section: The Second‐order Two‐step Fd Methodssupporting
confidence: 59%
“…Then the transformed problem has been solved by a well‐developed optimization algorithm. An iterative dynamic programming (IDP) is applied for the solution of TDOCPs in . Then Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The convergence is speeded up considerably by introducing the penalty term 0.01u 1 (t) 2 in the cost functional and deleting the terminal conditions. Dadebo and Luus [13] treat a similar CSTR with n = 4 state variables, but no delay in the control variable and no terminal conditions. Using a fine grid with N = 20 000, the CPU time for computing the optimal solution of this CSTR problem is in the range of a minute.…”
Section: Remarkmentioning
confidence: 99%
“…The iterative dynamic programming (IDP) is a variant of the standard approach allowing to come across these difficulties ( [15], [3]). By IDP, the problem is solved in a series of iterations rather than in a single pass of the DP algorithm.…”
Section: Iterative Dynamic Programmingmentioning
confidence: 99%